The effect of consistency on cache response time. - Dilley, J.
This report analyzes the impact of cache consistency on the response time of client requests. The analysis divides cache responses into classes according to whether or not the cache communicated with a remote server and whether or not object data was served from the cache. Analysis of traces from deployed proxy cache servers demonstrates that a round-trip to a remote server is the dominant factor for response time. This study concludes that improving cache consistency will reduce response time and allow a cache to serve more user requests
Keywords: World Wide Web; Cache consistency; Cache response time; Object data; Proxy cache servers; Remote server; Round-trip.